Venous blood gas parameters, electrolytes, glucose and lactate concentration in sick neonatal foals: Direct venipuncture versus push‐pull technique. (3rd September 2020) - Del Prete, Chiara; Lanci, Aliai; Cocchia, Natascia; Freccero, Francesca; Di Maio, Chiara; Castagnetti, Carolina; Mariella, Jole; Micieli, Fabiana
Abstract: Background: Blood collection by indwelling intravenous catheter (IVC) avoids repeated venipuncture, which could cause thrombophlebitis risk, anxiety and pain in patients. Objectives: To compare blood gas parameters, electrolytes, glucose, lactate and haematocrit concentration obtained from venous blood samples collected via a jugular IVC by push‐pull (PP) technique to those obtained by venipuncture in hospitalised foals, at the time of catheter placement (T0) and 24 hours after the beginning of intravenous therapy (T24). Study design: Prospective observational study. Methods: Paired blood samples were drawn from hospitalised foals at T0 and T24. In each foal, one venous blood sample was collected via IVC by the following PP technique: 2.4 mL of blood was aspirated and immediately reinfused through the catheter three times consecutively, then 1 mL of blood was collected using a 1 mL heparinised syringe. Thereafter, another sample was collected by direct venipuncture of the contralateral jugular vein, with an identical 1 mL heparinised syringe, with a 1‐inch, 20‐G needle. All samples were analysed with an automated blood gas analyser within 10 minutes of collection. The agreement between the two techniques was assessed by Bland‐Altman analysis and intraclass correlation coefficient (ICC). Results: The level of agreement of blood gas values obtained by the two different techniques was high with very small bias and clinically acceptable ICC (>0.907 at T0; >0.794 at T24) for all variables, except for haematocrit (bias −3.52 at T0; −2.44 at T24) and PvO2 at T0 and T24 (ICC 0.669 and 0.733, respectively). Main limitations: Potential sub‐clinical catheter‐related complications were not investigated by ultrasound or bacterial culture of the catheter; short duration of the study. Conclusions: PP technique appears to be acceptable for collection of blood samples for venous blood gas parameters, as well as electrolytes, glucose and lactate in sick neonatal foals.